(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
While maintaining worldwide racial reproduction hierarchy, India’s commercial surrogacy industry actually creates people and human connections. The forceful enemy of natalism of the post pilgrim state repeats the more extensive worldwide populace control plan, which outlines the worldwide South’s high fruitfulness rates as a "worldwide risk" that should be controlled no matter what, yet it is at chances with the neoliberal basic of unhindered worldwide ripeness the travel industry. Substitutes (belly mothers) upset male centric talks by recovering control of their bodies and giving their ripe bodies something to do. They ultimately stick to worldwide neo-eugenic objectives to diminish the richness of lower class ladies in the worldwide South by controlling their own propagation through decisions about ripeness, sanitization, and fetus removal to (re)produce posterity of higher classes and advantaged nations. Surrogates artistically create familial connections with the infant and the intended mother across class, caste, religion, race, and country, undermining dominant genetic and patriarchal underpinnings of kinship while essentially reifying systemic inequalities.